Pharmacological enhancement of leg and muscle microvascular blood flow does not augment anabolic responses in skeletal muscle of young men under fed conditions - Phillips, Bethan E.; Atherton, Philip J.; Varadhan, Krishna; Wilkinson, Daniel J.; Limb, Marie C.; Selby, Anna L.; Rennie, Michael J.; Smith, Kenneth; Williams, John P. (American Physiological Society, 2014)
Skeletal muscle anabolism associated with postprandial plasma aminoacidemia and insulinemia is contingent upon amino acids (AA) and insulin crossing the microcirculation-myocyte interface. In this study, we hypothesized that increasing muscle microvascular blood volume (flow) would enhance fed-state anabolic responses in muscle protein turnover. We studied 10 young men (23.2 ± 2.1 yr) under postabsorptive and fed [iv Glamin (∼10 g AA), glucose ∼7.5 mmol/l] conditions. Methacholine was infused into the femoral artery of one leg to determine, via bilateral comparison, the effects of feeding alone vs. feeding plus pharmacological vasodilation. We measured leg blood flow (LBF; femoral artery) by Doppler ultrasound, muscle microvascular blood volume (MBV) by contrast-enhanced ultrasound (CEUS), muscle protein synthesis (MPS) and breakdown (MPB; a-v balance modeling), and net protein balance (NPB) using [1,2-13C2]leucine and [2H5]phenylalanine tracers via gas chromatography-mass spectrometry (GC-MS). Indexes of anabolic signaling/endothelial activation (e.g., Akt/mTORC1/NOS) were assessed using immunoblotting techniques. Under fed conditions, LBF (+12 ± 5%, P < 0.05), MBV (+25 ± 10%, P < 0.05), and MPS (+129 ± 33%, P < 0.05) increased. Infusion of methacholine further enhanced LBF (+126 ± 12%, P < 0.05) and MBV (+79 ± 30%, P < 0.05). Despite these radically different blood flow conditions, neither increases in MPS in response to feeding (0.04 ± 0.004 vs. 0.08 ± 0.01%/h, P < 0.05) nor improvements in NPB (−4.4 ± 2.4 vs. 16.4 ± 5.7 nmol Phe·100 ml leg−1·min−1, P < 0.05) were affected by methacholine infusion (MPS 0.07 ± 0.01%/h; NPB 24.0 ± 7.7 nmol Phe·100 ml leg−1·min−1), whereas MPB was unaltered by either feeding or infusion of methacholine. Thus, enhancing LBF/MBV above that occurring naturally with feeding alone does not improve muscle anabolism.